A Theoretical study of thermodynamic properties of Cd-Bi liquid alloy - Adhikari, D (BIBECHANA, 2012)
Flory’s model has been used for the study of thermodynamic properties of Cd-Bi liquid alloys. Free energy of mixing, heat of mixing, entropy of mixing and activity of Cd have been determined. All of these computed quantities have been found to be in a good agreement with observed values. Keywords: Flory’s model; thermodynamic properties; Cd-Bi liquid alloy; weakly interacting system; interaction energy parameter DOI: http://dx.doi.org/10.3126/bibechana.v8i0.5693 BIBECHANA 8 (2012) 90-95